(Non)-transparent biography. Leopold Staff`s casus - Wójcik, Tomasz (Biografie nieoczywiste: Przełom, kryzys, transgresja w perspektywie interdyscyplinarnej, 2018)
The subject of reflection is a special casus of Leopold Staff’s biography. The author contemplates him in the perspective of a biographical anti-legend (Staff as a writer without a biography) and creative legend (Staff as a model of a pure poet). He questions the dichotomy of a private biography of a human and the artistic biography of a writer in order to search the essence of the Willow`s author biography between them.